ISU GLOBAL PEREKONOMIAN ISLAM: Telaah Kritis terhadap Tata Kelola dan Aktivitas Lembaga-lembaga Keuangan Islam - Muhdi Kholil (JESI (Jurnal Ekonomi Syariah Indonesia), 2011)
Indonesia is to be known widely by the world, which has Islamic finance system different from most countries. Indonesia which is in the international forum of financial syriah known "orthodox" or conservative in the application of Islamic principles recognized the economic practice of Islam which is closer to the economic substance of Islam, and relatively completed all aspects of the economy. Islamic economic development not only in the sectors has been developed such as banking, capital markets and non-bank financial institutions other, but also in extended development of the microfinance sector,  social and financial practices of real business to meet Islamic principles.The composition and transaction of Islamic financial products’ Indonesia is a fact that is not owned by other countries which are also developing Islamic banking and finance industry. No wonder, since the majority of developing countries in the world of sharia finance industry with the approach of imitation (mimicry) with conventional, and many experts doubt the originality/economic system of Islamic finance, both conventional and expert on Islamic scholars. But on many opportunities, from seminars, conferences and working group forum, many countries are aware that Indonesia has a different form of sharia industry, the application of Islamic finance that has another color.Keyword: Economics, Sharia, Indonesia.